THE ROLE OF HUMAN RESOURCE MANAGEMENT IN IMPROVING ORGANIZATION PERFORMANCE (A LITERATURE REVIEW) - Prayudo, Gito; Tukiran, Martinus (International Journal of Multidisciplinary Research and Literature, 2024)
This study aims to explore the role of human resource management (HRM) in improving organizational performance. The main focus of this study includes proper recruitment management, employee development, HR planning, knowledge management, conflict management, and competitive compensation systems. The study's findings suggest that organizations can enhance their productivity and efficiency by implementing effective HRM practices, including selecting employees who align with their culture, providing pertinent training, and managing knowledge. Integrating HRM planning with organizational strategy also contributes to attaining long-term objectives and enhanced competitiveness. This study also emphasizes the importance of constructive conflict management and fair compensation systems in improving employee motivation and retention. In the midst of globalization, organizations that can adapt their HR to the demands of the global market will be superior in competition. In conclusion, this investigation substantiates the notion that effective human resource management (HRM) facilitates employee management and the formulation organizational strategies that facilitate long-term success